Expectations of Facebook users towards a virtual dialogue with their public utility. Issue 3 (30th May 2018) - Martin, Sebastian; Greiling, Dorothea; Wetzelhütter, Daniela
Abstract : Purpose: A growing amount of German and Austrian utilities create own Facebook accounts to communicate with their stakeholders. Whereas existing studies describe how utility companies are currently using Facebook, to the best of the authors' knowledge, there exists no study which focuses on the actual expectations of Facebook users. Nevertheless, as the occurrence of social media redefined stakeholders' expectations, research on the expectations of Facebook users become crucial. Therefore, the purpose of this paper is to contribute to the existing social media literature by investigating the expectations of Facebook users towards a virtual stakeholder dialogue with their public utility companies on Facebook. Design/methodology/approach: Eight German and six Austrian public utilities supported the empirical study by posting a link to an online survey on their Facebook account. In total, 258 Facebook users followed that link and completed the survey. Findings: The broad majority of participants expect public utility companies to use Facebook as a communication channel. They request to regularly receive a variety of information on different topics. In addition, participants want to have the opportunity to post general queries, complaints or criticism, suggestions for improvement, positive feedback or queries in a crisis situation. Moreover, the empirical data reveal that user-specific characteristics such as gender, age, country of residence, length of Facebook membership or number of Facebook friends impact the expectations towards a Facebook conversation. Originality/value: The findings enable scholars and practitioners to gain in-depth insights into Facebook conversations from the actual user perspective.